DrugTargetInspector: An assistance tool for patient treatment stratification. Issue 7 (21st January 2016) - Schneider, Lara; Stöckel, Daniel; Kehl, Tim; Gerasch, Andreas; Ludwig, Nicole; Leidinger, Petra; Huwer, Hanno; Tenzer, Stefan; Kohlbacher, Oliver; Hildebrandt, Andreas; Kaufmann, Michael; Gessler, Manfred; et al.
Abstract : Cancer is a large class of diseases that are characterized by a common set of features, known as the Hallmarks of cancer . One of these hallmarks is the acquisition of genome instability and mutations. This, combined with high proliferation rates and failure of repair mechanisms, leads to clonal evolution as well as a high genotypic and phenotypic diversity within the tumor. As a consequence, treatment and therapy of malignant tumors is still a grand challenge. Moreover, under selective pressure, e.g ., caused by chemotherapy, resistant subpopulations can emerge that then may lead to relapse. In order to minimize the risk of developing multidrug‐resistant tumor cell populations, optimal (combination) therapies have to be determined on the basis of an in‐depth characterization of the tumor's genetic and phenotypic makeup, a process that is an important aspect of stratified medicine and precision medicine. We present DrugTargetInspector (DTI), an interactive assistance tool for treatment stratification. DTI analyzes genomic, transcriptomic, and proteomic datasets and provides information on deregulated drug targets, enriched biological pathways, and deregulated subnetworks, as well as mutations and their potential effects on putative drug targets and genes of interest. To demonstrate DTI's broad scope of applicability, we present case studies on several cancer types and different types of input ‐omics data. DTI's integrative approach allows users to characterize the tumor under investigation based on various ‐omics datasets and to elucidate putative treatment options based on clinical decision guidelines, but also proposing additional points of intervention that might be neglected otherwise. DTI can be freely accessed athttp://dti.bioinf.uni‐sb.de . Abstract : What's New? The extreme molecular diversity of tumors is a major obstacle to the precise stratification and treatment of cancers, and to overcome it, clinicians have increasingly turned to in‐depth genotypic and phenotypic tumor characterization. To assist in that process, the authors of the present study developed DrugTargetInspector (DTI), a web‐based tool suite that analyzes patient‐specific –omics datasets for the identification of tumor characteristics and relevant treatment options. DTI draws on information from across multiple databases to detect mutations, deregulated drug targets, and recommended drug options. The platform is a valuable addition to existing decision‐support mechanisms for cancer therapy.